The utility of strain imaging in the cardiac surveillance of bone marrow transplant patients. Issue 7 (22nd July 2021) - Deshmukh, Tejas; Emerson, Peter; Geenty, Paul; Mahendran, Shehane; Stefani, Luke; Hogg, Megan; Brown, Paula; Panicker, Shyam; Chong, James; Altman, Mikhail; Gottlieb, David; Thomas, Liza
Abstract : Objective: To evaluate the utility of two-dimensional multiplanar speckle tracking strain to assess for cardiotoxicity post allogenic bone marrow transplantation (BMT) for haematological conditions. Methods: Cross-sectional study of 120 consecutive patients post-BMT (80 pretreated with anthracyclines (BMT+AC), 40 BMT alone) recruited from a late effects haematology clinic, compared with 80 healthy controls, as part of a long-term cardiotoxicity surveillance study (mean duration from BMT to transthoracic echocardiogram 6±6 years). Left ventricular global longitudinal strain (LV GLS), global circumferential strain (LV GCS) and right ventricular free wall strain (RV FWS) were compared with traditionl parameters of function including LV ejection fraction (LVEF) and RV fractional area change. Results: LV GLS (−17.7±3.0% vs −20.2±1.9%), LV GCS (−14.7±3.5% vs −20.4±2.1%) and RV FWS (−22.6±4.7% vs −28.0±3.8%) were all significantly (p=0.001) reduced in BMT+AC versus controls, while only LV GCS (−15.9±3.5% vs −20.4±2.1%) and RV FWS (−23.9±3.5% vs −28.0±3.8%) were significantly (p=0.001) reduced in BMT group versus controls. Even in patients with LVEF >53%, ~75% of patients in both BMT groups demonstrated a reduction in GCS. Conclusion: Multiplanar strain identifies a greater number of BMT patients with subclinical LV dysfunction rather than by GLS alone, and should be evaluated as part of post-BMT patient surveillence. Reduction in GCS is possibly due to effects of preconditioning, and is not fully explained by AC exposure.